Effect of Social Capital on Firm Performance: The Role of Entrepreneurial Orientation and Dynamic Capability - Hongyun, Tian; Kankam, William Adomako; Appiah-Twum, Florence; Akolgo, Isaac Gumah (International Review of Management and Marketing, 2019)
Social capital is a concept that describes good quality social relations that can lead to mutual benefits. The social capital theory thrives on relationships in networks to gain access to resources, especially information benefits not available to non-members of the network. The study reports the effects of social capital on firm performance. The study further examines the moderating role of entrepreneurial orientation in the relationship between social capital and firm performance; and the mediating role of dynamic capabilities in the relationship between social capital and firm performance. Using SmartPLS software 3.2.8 to analyze primary data collected from 787 small and medium-sized enterprises (SMEs) operating in Ghana, the results show that social capital has a positive and direct relationship with firm performance in Ghana. The findings suggest that EO moderates the relationship between social capital and firm performance. Again, dynamic capabilities mediate the relationship between social capital and firm performance. The study also provides managers with practical ways of building relationships within their networks for achieving competitive advantage in the current business environment. Keywords: Social capital, Entrepreneurial Orientation, Dynamic capabilities and firm performance JEL Classifications: L31, M1 DOI: https://doi.org/10.32479/irmm.8108